Hubungan pengetahuan ibu tentang perawatan bayi berat lahir rendah (BBLR) dengan kenaikan berat badan bayi - Sri Ratna Ningsih; Purnomo Suryantoro; Evi Nurhidayati (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2016)
Abstrack: The objective of the research is to know the correlation between mother’s knowledge about the treatment of LBW and baby’s weight gain at RSUD Wates in 2016. This research is a correlative-descriptive research using cross sectional time approach. The population of this research was mothers who have LBW, and 59 respondents were selected using quota sampling. This research uses questionnaire to get the data and chi-square for analysis test. Test the validity of using Product Moment correlation and Cronbach Alpha reliability test with. The research result is mother’s knowledge in gaining weight to Low Birth Weight. Therefore, it is hoped that mother whose baby is LBW can enrich knowledge especially is managing correct breastfeeding.